Jordanian Kindergarten and 1st-Grade Teachers' Beliefs About Child-Based Dimensions of School Readiness. Issue 3 (2nd July 2016) - Fayez, Merfat; Ahmad, Jamal Fathi; Oliemat, Enass
ABSTRACT: The purpose of this study was to explore the beliefs of Jordanian kindergarten and 1st-grade teachers regarding six child-based dimensions of school readiness: academic knowledge, basic thinking skills, socioemotional maturity, physical well-being and motor development, self-discipline, and communication skills. Questionnaires were used to collect data from 289 teachers; 155 kindergarten teachers and 134 1st-grade teachers were randomly selected from Zarqa, a highly populated city in Jordan. Results revealed that kindergarten and 1st-grade teachers considered all the six child-based dimensions as important to getting children ready for school. However, both groups of teachers rated the basic academic knowledge as the most important dimension and emphasized it over the other dimensions. In addition, results of the multivariate analysis of variance (MANOVA) indicated that there were statistically significant differences in the beliefs of kindergarten and 1st-grade teachers on four dimensions: academic knowledge, basic thinking skills, socioemotional development, and communication skills; meaning that kindergarten teachers rated these dimensions as more important than 1st-grade teachers did. Yet when teachers' level of education was controlled for as a covariate, multivariate analysis of covariance results showed that significant statistical differences were only detected on the first dimension (i.e., academic knowledge). Suggestions for policymakers and for further research were offered based on the results of this study.